2020
DOI: 10.1213/ane.0000000000005044
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Monocytic Human Leukocyte Antigen-DR Expression Indicates Immunosuppression in Critically Ill COVID-19 Patients

Abstract: This author helped with the conception and design of the study, analysis and interpretation of data, drafting the article, and approved the final version to be submitted. Conflicts of Interest: T. Spinetti declares that the Department of Intensive Care Medicine, Inselspital, Bern, has received research or other grants from (full departmental disclosure):

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 28 publications
9
67
0
Order By: Relevance
“…Four were based on values obtained using a standardized protocol and results are expressed as the number of antibodies bound per cell (AB/C). Most importantly, these independent studies from different groups located in different countries (Bern‐CH, Nijmegen‐NL, Limoges‐F, Lyon‐F) provided extremely homogenous results (27–30). Initial mHLA‐DR values for ICU COVID‐19 patients were around 10,000 AB/C, which was lower than controls (>15,000 AB/C) but not as low as that found in septic shock (around 5,000 AB/C).…”
Section: Clinical Results In Covid‐19 Patientsmentioning
confidence: 99%
“…Four were based on values obtained using a standardized protocol and results are expressed as the number of antibodies bound per cell (AB/C). Most importantly, these independent studies from different groups located in different countries (Bern‐CH, Nijmegen‐NL, Limoges‐F, Lyon‐F) provided extremely homogenous results (27–30). Initial mHLA‐DR values for ICU COVID‐19 patients were around 10,000 AB/C, which was lower than controls (>15,000 AB/C) but not as low as that found in septic shock (around 5,000 AB/C).…”
Section: Clinical Results In Covid‐19 Patientsmentioning
confidence: 99%
“…Additionally, Hoffmann et al ( 44 ) found that reduced monocytic human leukocyte antigen-DR (HLA-DR), led by SIDS, could predict SAP independently. During the novel coronavirus 2019 pandemic, a new study found that decrease depression of monocytic HLA-DR in critically ill patients may lead to immunosuppression ( 46 ). Thus, we hypothesized that SIDS would decrease the expression of monocytic HLA-DR and compensatively increase monocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, successful completion of a clinical trial for PD-L1 in sepsis could also be tested as a therapy for COVID-19–related immunosuppression. Given results obtained by Spinetti et al, 1 this seems to be a relevant approach to diminishing morbidity and mortality among ICU patients with COVID-19. Another potential benefit is utilization of HLA-DR variants as a prognostic tool to identify individuals with a higher risk for severe infection and hospitalization due to COVID-19.…”
mentioning
confidence: 88%
“…Despite remarkable progress in understanding the immune response to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), optimal management of immune function during severe viral infections remains a major issue among critically ill patients. In this issue of Anesthesia & Analgesia , a clinical study by Spinetti et al 1 revealed serious concerns about the development of immunosuppression among coronavirusdisease2019 (COVID-19) patients requiring hospitalization in an intensive care unit (ICU). A significant number of patients appeared to develop immune dysfunction, as evidenced by reduced amounts of monocytic human leukocyte antigen-DR (mHLA-DR).…”
mentioning
confidence: 99%